Developing a research diagnostic criteria for burning mouth syndrome: Results from an international Delphi process. (19th November 2020) - Currie, Charlotte C.; Ohrbach, Richard; De Leeuw, Reny; Forssell, Heli; Imamura, Yoshiki; Jääskeläinen, Satu K.; Koutris, Michail; Nasri‐Heir, Cibele; Huann, Tan; Renton, Tara; Svensson, Peter; Durham, Justin
Abstract: Objective: To develop a beta version of a preliminary set of empirically derived research diagnostic criteria (RDC) for burning mouth syndrome (BMS) through expert consensus, which can then be taken into a test period before publication of a final RDC/BMS. Design: A 6 round Delphi process with twelve experts in the field of BMS was used. The first round formed a focus group during which the purpose of the RDC and the definition of BMS was agreed upon, as well as the structure and contents. The remaining rounds were carried out virtually via email to achieve a consensus of the beta version of the RDC/BMS. Results: The definition of BMS was agreed to be 'an intraoral burning or dysaesthetic sensation, recurring daily for more than 2 hours per day over more than 3 months, without evident causative lesions on clinical examination and investigation'. The RDC was based upon the already developed and validated RDC/TMD and formed three main parts: patient self‐report; examination; and psychosocial self‐report. A fourth additional part was also developed listing aspirational biomarkers which could be used as part of the BMS diagnosis where available, or to inform future research. Conclusion: This Delphi process has created a beta version of an RDC for use with BMS. This will allow future clinical research within BMS to be carried out to a higher standard, ensuring only patients with true BMS are included. Further validation studies will be required alongside refinement of the RDC as trialling progresses.